Writing e-mails that have a clear purpose - Canavor, Natalie 1942- (Pearson Education Pub. as FTPress Delivers, 2010)
"Make sure every email has a purpose--and your message is instantly clear to everyone you're sending it to. If you liked this Element, read more from Natalie Canavor and Claire Meirowitz, including The Truth About the New Rules of Business Writing (ISBN: 9780137153152)."--Resource description page